Development and validation of a Model of Technology-Supported Learning for Special Educational Needs Learners in Malaysian institutions of higher learning / Roslinda Alias - Alias, Roslinda (Institute of Graduate Studies, UiTM, 2016)
This study is intended to develop and validate the Model of Technology- Supported Learning for Special Educational Needs (SEN) Learners in Malaysian institutions of higher learning (IHLs). This is due to the lack of technological-research based on the SEN learners particularly in IHLs in Malaysia. Utilizing the design and development research (DDR) approach, this study comprises three phases. The first phase of the study is the needs assessments and model development. Needs assessments were conducted among the eight public as well as 66 SEN learners from eight selected Malaysian IHL through interview as well as an adapted and validated questionnaire. Content analysis on the selected Malaysian IHLs’ websites was carried out for the initial foundation of the prototype for the Model. Information from needs assessments, content analysis and literature review was then used to develop an initial extensive prototype of the Model of Technology-Supported Learning for SEN Learners. The second phase of the study is the Model validation, involves a heterogeneous group of subject matter experts (SMEs). Eleven SMEs were involved in validating the Model through Delphi technique…